Review of the Nanostructuring and Doping Strategies for High-Performance ZnO Thermoelectric Materials - Suraya, Sulaiman; Izman, Sudin; Al-Naib, Uday M. Basheer; Muhammad Firdaus, Omar (MDPI AG, 2022)
Unique properties of thermoelectric materials enable the conversion of waste heat to electrical energies. Among the reported materials, Zinc oxide (ZnO) gained attention due to its superior thermoelectric performance. In this review, we attempt to oversee the approaches to improve the thermoelectric properties of ZnO, where nanostructuring and doping methods will be assessed. The outcomes of the reviewed studies are analysed and benchmarked to obtain a preliminary understanding of the parameters involved in improving the thermoelectric properties of ZnO